Pediatric acute osteomyelitis in the postvaccine, methicillin-resistant Staphylococcus aureus era - Ratnayake, Kristin; Davis, Andrew J.; Brown, Lance; Young, Timothy P. (The American journal of emergency medicine, 2015)
We sought to describe the causative organisms, bones involved, and complications in cases of pediatric osteomyelitis in the postvaccine age and in the era of increasing infection with community-associated methicillin-resistant Staphylococcus aureus (MRSA). We reviewed the medical records of children 12 years and younger presenting to our pediatric emergency department between January 1, 2003, and December 31, 2012, with the diagnosis of osteomyelitis. We reviewed operative cultures, blood cultures, and imaging studies. We identified causative organisms, bone(s) involved, time to therapeutic antibiotic treatment, and local and hematogenous complications. The most common organism identified was methicillin-sensitive S aureus (26/55), followed by MRSA (21/55). Seventy-three bone areas were affected in 67 subjects. The most common bone area was the femur (24/73). Forty-six subjects had 75 local complications. The most common organism in cases with local complications was MRSA (49%). Three subjects had hematogenous complications of deep venous thrombosis, septic pulmonary embolus, and endophthalmitis. Subjects with complications had shorter time to therapeutic antibiotic treatment. When an operative culture was done after therapeutic antibiotics were given, an organism was identified from the operative culture in 84% of cases. Treatment of pediatric osteomyelitis should include antibiotic coverage for MRSA. Most cases of pediatric osteomyelitis occur in the long bones. Hematogenous complications may include deep venous thrombosis and may be related to treatment with a central venous catheter. Operative culture yield when antibiotics have already been given is high, and antibiotic treatment should not be delayed until operative cultures are obtained.